Pengaruh Kualitas Produk, Harga, Citra Merek, dan Brand Trust Terhadap Keputusan Pembelian Produk Hand & Body Lotion Marina - Salma Luthfiyah Agustin; Mirza Mirza (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine and analyze the influence of product quality, price, brand image, and brand trust on purchasing decisions for Marina hand & body lotion products. Marina hand & body lotion products are one of the body care products that are quite popular among Indonesian consumers, especially in urban areas. Increasingly tight competition in the cosmetics and personal care industry encourages companies to continue to pay attention to factors that can influence consumer behavior in making purchasing decisions. Therefore, this study focuses on four main variables that are considered to play an important role, namely product quality, price, brand image, and brand trust. The type of research used is quantitative research with a data collection method through the distribution of online questionnaires using Google Forms. The population in this study were consumers in the DKI Jakarta area who have used Marina hand & body lotion products. The sampling technique was carried out using purposive sampling, where respondents were selected based on certain criteria, namely having used Marina products. The number of samples used refers to the Hair formula, resulting in a sample size of 210 respondents. The collected data were then analyzed using the Partial Least Square (PLS) method with the aim of testing the relationship between variables simultaneously and partially. The results of the study indicate that product quality, price, brand image, and brand trust have a positive and significant influence on purchasing decisions for Marina hand & body lotion products. This means that the higher consumers' perceptions of product quality, price suitability, good brand image, and level of trust in the Marina brand, the greater the likelihood of consumers deciding to make a purchase. These findings indicate that companies need to maintain consistent product quality, set competitive prices, strengthen brand image through effective marketing strategies, and increase brand trust through innovation and transparent communication.